Огляд джерел до історії запорозького гайдамацтва XVIII століття в архівосховищах Польщі. (Zaporizhzhia Historical Review, 2021)
The article describes the main collections of documental, narrative and over primary sources to history of Zaporozhzhian Hajdamaks during the XVIII age, which situated in Polish archives and libraries.